Mulakhaṣāt al-Rasā’il al-‘Ilmiyyah (al-Dukturah) li Qism al-‘Aqīdah wa al-Fikr al-Islamī Ᾱkādemiyyah al-Dirāsāt al-Islamiyyah bi Jāmi‘ah Malayā al-Ḥalaqah al-Ūlā sanah 2006/2007M - Muá¹£á¹afÄ Bahjat, MujÄhid; á¸¤Ämid, Muá¸¥ammad Fawzi (Jurnal Usuluddin, 2005)
This paper discusses a number of PhD theses submitted to the Department of Aqidah and Islamic Thought in 2006 and 2007. They are eight theses on a variety of topics: Dogmatic Approach from the Perspective of Hamka, Al-Tawheed from the Perspective of Ibn Taymiyya, The Concept of Aqidah in the Minds of Malawians, in Psychotherapy, in the Shiite ideology, in the Customs and Traditions, in Prohibited Doctrines, and in the Chinese Religious Thought. As theses are composed in Bahasa Malay. in our study, we present their Abstract to show their significance, objectives, methodology, findings, and finally the contents of the sections and chapters.